Optimising UK urban road verge contributions to biodiversity and ecosystem services with cost-effective management. (15th April 2017) - O'Sullivan, Odhran S.; Holt, Alison R.; Warren, Philip H.; Evans, Karl L.
Abstract: Urban road verges can contain significant biodiversity, contribute to structural connectivity between other urban greenspaces, and due to their proximity to road traffic are well placed to provide ecosystem services. Using the UK as a case study we review and critically evaluate a broad range of evidence to assess how this considerable potential can be enhanced despite financial, contractual and public opinion constraints. Reduced mowing frequency and other alterations would enhance biodiversity, aesthetics and pollination services, whilst delivering costs savings and potentially being publically acceptable. Retaining mature trees and planting additional ones is favourable to residents and would enhance biodiversity, pollution and climate regulation, carbon storage, and stormwater management. Optimising these services requires improved selection of tree species, and creating a more diverse tree stock. Due to establishment costs additional tree planting and maintenance could benefit from payment for ecosystem service schemes. Verges could also provide areas for cultivation of biofuels and possibly food production. Maximising the contribution of verges to urban biodiversity and ecosystem services is economical and becoming an increasingly urgent priority as the road network expands and other urban greenspace is lost, requiring enhancement of existing greenspace to facilitate sustainable urban development. Highlights: Urban road verges are often overlooked when discussing urban greenspace. Verges can contribute significantly to urban biodiversity and ecosystem services. Contractual obligations and public reaction concerns limit current contributions. Current planting schemes, and tree species selection, further limit contributions. Alternative management can cost-effectively enhance biodiversity & ecosystem services.